The Impact on Community Mobility during the Pandemic Crisis in Romania - Denis-Cătălin ARGHIR (Communications of International Proceedings, 2021)
The technological evolution of the last years cumulated with the development in the field of mobile devices, such as smartphones, has generated profound changes in the economy, but also in society. Increasing the availability of mobile devices has led to the generation of large packets of data on user behavior. In the fight against the COVID-19 pandemic, anonymized aggregate data on population movement began to be made public by giants Google, Apple and Waze in reports showing mobility trends, on driving or pedestrian movements. In the current epidemic context, these data can be valuable sources to be used in measuring the application of social distancing restrictions, but also for developing the resilience of communities to cope and learn based on the response of the population to the various waves of the pandemic. The data were tracked for the period before the national lockdown in Romania, during the state of emergency and during the state of alert. Descriptive statistics were applied, represented in various diagrams, such as boxplot type diagrams, Heat Stream representations; also correlation and regression analysis was performed to test the existence and strength of the linear relation between the variables represented by mobility data and those related to SARS-COV-2 virus infection obtained from official statistics.
Keywords: mobility; Covid-19 pandemic; lockdown impact; community resilience